DAYA DUKUNG SARANA DAN PRASARANA SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA - Iyon Muhdiyati; Rizal Septiadi (LPPM Universitas Bina Bangsa, 2023)
Infrastructure facilities are equipment and supplies that are directly used and support the educational process, especially the teaching and learning process such as buildings, classrooms, tables, chairs, as well as teaching tools and media. learning motivation is the entire psychic driving force that exists in individual students that can provide encouragement to learn in order to achieve the goals of learning. This study aims to: 1. Describe how the use of infrastructure for learning motivation for students, 2. Describe the learning motivation of students t SDN Cimande 02, 3. The carrying capacity of facilities and infrastructure on student learning motivation. This research was carried out at SDN Cimande 02. The subjects of this study were class V participants at SDN Cimande 02 in the form of 3 people. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews and documentation techniques. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The final result of this study shows that students at SDN Cimande 02 can take advantage of the facilities and infrastructure provided by the school as a tool that can motivate their learning